Contemporary Perspectives on Nazi Germany. Issue 2 (1st June 2019) - Bendix, John
Abstract : Paul Roland, Life in the Third Reich: Daily Life in Nazi Germany, 1933-1945 (London: Arcturus Publishing, 2015) Eric Kurlander, Hitler's Monsters: A supernatural history of the Third Reich (New Haven: Yale University Press, 2017) Shelley Baranowski, Armin Nolzen, and Claus-Christian W. Szejnmann, A Companion to Nazi Germany (Hoboken: Wiley, 2018)